The need to improve the family cases management system in Malaysia’s syariah courts - Farah Safura Muhammud; Rafeah Saidon; Ahmad Faizal Ramly; Norazla Abdul Wahab; Nur Ain Nazifa Mohd Zawawi (Penerbit Universiti Kebangsaan Malaysia, 2024)
The increase in family cases today, including domestic violence, failure to pay alimony, infidelity, polygamy without consent, and others, has drawn attention from the public on social media, not to mention the involvement of well known influencers and celebrities. A total of 19,268 cases of domestic violence were reported between 2020 and 2022 (Royal Malaysia Police) (PDRM). In 2020, 5,260 cases were recorded, followed by 7,468 cases in 2021 and 6,540 cases in 2022. When legal action is taken against religious organizations and the government, the situation becomes further tense. The credibility of Malaysia’s Islamic judicial institutions will erode if this predicament remains. The Malaysian Syariah Justice Department (JKSM), the Malaysian Islamic Development Department (JAKIM), the Royal Malaysian Police (PDRM), and Bank Negara are among the various organizations involved in these cases. Is there a consistent system in place across Malaysia’s different justice institutions? Consequently, the purpose of this study is to determine whether there is a need to enhance Malaysia’s data management system for Islamic family issues. This qualitative research involved five of the highest-ranking JKSM officers being subjected to in-depth interviews with a line of questions that had been carefully selected and aligned with the study’s objective. A theoretical framework model of Islamic family management was created based on the thematic analysis of the findings. The research findings suggest that there is a significant need to improve the management of family cases in the Syariah Court, including the need to improve the record system and technology between Malaysia’s Syariah Courts. This advancement is significant because it contributes to the development of a Civilized Malaysian and is in line with Malaysia Madani proposed by Malaysia Prime Minister, which prioritizes the development of socially prosperous Malaysian families and communities.